Impacts of System Quality and Service Quality toward Tokopedia’s Customer Loyalty with Customer Satisfaction as the Mediating Variable - Anton Darius Darmawan; Theo Sudono (iBuss Management, 2022)
Further advancement of information and communication technology in Indonesia can be seen through the number of Indonesian users of the internet in the country, which have increased significantly up until 2021. This further supports the use of internet-based activities, including utilizing digital means of conducting transactions, through e-commerce platforms. As more citizens are using e-commerce in the market, competitiveness between these platforms becomes more prominent. Tokopedia as one of the existing e-commerce platforms has managed to regain its position as the number one most visited e-commerce platform since the first quarter 2021, after losing to another major e-commerce platform, Shopee, during the whole year of 2020. By conducting this study, the researchers would like to know whether system quality and service quality are affecting the Tokopedia application users to stay loyal in using the platform since customers who shop online tend to switch easily among e-commerce platforms, with satisfaction as the mediating variable. This research’s sampling design will be probability sampling, specifically on simple random sampling. Furthermore, 135 respondents were taken into account and analyzed using PLS-SEM and bootstrapping method, where the results shows that system quality and service quality are mediated by customer satisfaction in influencing Tokopedia users’ loyalty.Keywords: System quality, Service quality, Customer satisfaction, Customer loyalty